Penerapan Model PBL Berbantu Papan Tempel Keragaman Budaya Indonesia untuk Meningkatkan Hasil Belajar literasi menulis pada Mata Pelalajaran Pendidikan Pancasila Siswa Kelas IV SDN MLATIHARJO 02 - Esin Quroesin; Finerefinne Finerefinne (Departement of Mathematics Education, 2024)
This research aims to enhance the writing literacy of fourth-grade students at SDN Mlatiharjo 02 Semarang in Pancasila Education through the use of sticky boards. The study employs Classroom Action Research (CAR) methodology. Data collection was conducted using observations and tests, and the data were analyzed through comparative descriptive analysis based on the percentage of student learning outcomes. The findings indicate that using sticky boards in Pancasila Education lessons significantly improves students' understanding of the Indonesian Cultural Diversity material. By having teachers and students place various norms on the sticky boards to illustrate the examples, the learning outcomes of the students improved. This improvement is demonstrated by the increased percentage of students meeting the KKTP criteria. Before the intervention, only 15% of students met the KKTP standards with an average score of 77, while 85% did not. After the implementation of the PBL model supported by the sticky board on Indonesian Cultural Diversity, the average score rose to 88, with 100% of the students meeting the standards.